ANALISIS UNSUR SOSIAL BUDAYA DALAM TEKS DRAMA “PANEMBAHAN RESO” KARYA W.S. RENDRA SEBAGAI ALTERNATIF PEMILIHAN BAHAN AJAR DI KELAS XI - Deana Hanifa Jati Asmara; Titin Nurhayatin; Adi Rustandi (STKIP Subang, 2023)
Learning literature in education is presented in an integrated manner with language learning. This has an impact on the imbalance in the presentation of the weight of the material being taught between language learning and literature learning. So that many students do not understand the teaching of Indonesian literature. The formulation of the problem to be discussed in this study is formulated as follows. (1) how are the extrinsic elements related to socio-culture contained in the drama text Panembahan Reso by W.S. Rendra? (2) can the drama text Panembahan Reso by W.S. Rendra be used as an alternative for selecting Indonesian language teaching materials in class XI according to the demands of the 2013 curriculum? Based on these problems, this study aims to describe (1) the extrinsic socio-cultural elements in drama texts; (2) the drama text Panembahan Reso by W.S.Rendra as an alternative to selecting Indonesian language teaching materials in class XI according to the demands of the 2013 curriculum. This research method uses a qualitative descriptive method. The research data is in the form of extrinsic socio-cultural elements in the drama text Panembahan Reso by W.S. Rendra. The primary data source in this study is the drama text Panembahan Reso by W.S. Rendra. Secondary data sources in the form of books, scientific journals, websites that support research.